FAKTOR-FAKTOR YANG MEMPENGARUHI INTENSITAS PERILAKU WAJIB PAJAK DALAM PENGGUNAAN E-FILING PADA KANTOR PELAYANAN PAJAK MADYA MAKASSAR. - Asbi Amin (AkMen JURNAL ILMIAH, 2017)
This study aims to improve system quality, information quality, usability, ease and user satisfaction of interest in the use of e-filing at KPP Madya Makassar This study uses primary data by conducting direct research in the field by providing questionnaires / questionnaires to 92 respondents from taxpayers bodies registered in KPP Madya Makassar who want to be respondents. Data analysis method used is multiple linear regression analysis. The result of research shows that system quality, information quality, usability, ease and user satisfaction have a positive and significant effect to competition in KPP Madya Makassar.